Inhibitory effect and mechanism of gelatin stabilized ferrous sulfide nanoparticles on porcine reproductive and respiratory syndrome virus - Ting Tong; Shuangfei Deng; Xiaotong Zhang; Liurong Fang; Jiangong Liang; Shaobo Xiao (Journal of Nanobiotechnology, 2022)
Abstract Background The infection and spread of porcine reproductive and respiratory syndrome virus (PRRSV) pose a serious threat to the global pig industry, and inhibiting the viral infection process is a promising treatment strategy. Nanomaterials can interact with viruses and have attracted much attention due to their large specific surface area and unique physicochemical properties. Ferrous sulfide nanoparticles (FeS NPs) with the characteristics of high reactivity, large specific surface area, and low cost are widely applied to environmental remediation, catalysis, energy storage and medicine. However, there is no report on the application of FeS NPs in the antiviral field. In this study, gelatin stabilized FeS nanoparticles (Gel-FeS NPs) were large-scale synthesized rapidly by the one-pot method of co-precipitation of Fe2+ and S2‒. Results The prepared Gel-FeS NPs exhibited good stability and dispersibility with an average diameter of 47.3 nm. Additionally, they were characterized with good biocompatibility and high antiviral activity against PRRSV proliferation in the stages of adsorption, invasion, and replication. Conclusions We reported for the first time the virucidal and antiviral activity of Gel-FeS NPs. The synthesized Gel-FeS NPs exhibited good dispersibility and biocompatibility as well as effective inhibition on PRRSV proliferation. Moreover, the Fe2+ released from degraded Gel-FeS NPs still displayed an antiviral effect, demonstrating the advantage of Gel-FeS NPs as an antiviral nanomaterial compared to other nanomaterials. This work highlighted the antiviral effect of Gel-FeS NPs and provided a new strategy for ferrous-based nanoparticles against PRRSV. Graphical Abstract